2015
DOI: 10.1371/journal.pone.0140357
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Influence of Altruistic Behavior in a Social Network

Abstract: Prior research has suggested that recipients of generosity behave more generously themselves (a direct social influence). In contrast, there is conflicting evidence about the existence of indirect influence (i.e., whether interacting with a recipient of generosity causes one to behave more generously), casting doubt on the possibility that altruistic behavior can cascade through social networks. The current study investigated how far selfish and generous behavior can be transmitted through social networks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
11
1
Order By: Relevance
“…This study has several findings that should be noted ( Fig 2 ). While some of the relational paths identified in this work are not yet fully supported by the existing literature in the health sector, they are similar to those found in other domains, including the positive relationship between altruism and morale [ 71 , 72 ], the positive relationship between altruism and social support [ 73 , 74 ], and the positive relationship between altruism and job satisfaction [ 75 ]. Notably, the relationship between altruism and morale was the strongest among all the direct paths toward morale in the model.…”
Section: Discussionmentioning
confidence: 51%
“…This study has several findings that should be noted ( Fig 2 ). While some of the relational paths identified in this work are not yet fully supported by the existing literature in the health sector, they are similar to those found in other domains, including the positive relationship between altruism and morale [ 71 , 72 ], the positive relationship between altruism and social support [ 73 , 74 ], and the positive relationship between altruism and job satisfaction [ 75 ]. Notably, the relationship between altruism and morale was the strongest among all the direct paths toward morale in the model.…”
Section: Discussionmentioning
confidence: 51%
“…Yang, Liu and Zhou [21] showed that online social support could significantly account for altruistic behavior in the Internet. Liu, Safin, Yang, and Luhmann's data [22] revealed that an alternative expectation-based mechanism by which social interaction may influence altruistic behavior. Results from Liu, Xu, Liu, and Liu [23] suggested that online social support positively predicted online altruistic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…As behavior propagates in the social network, the behavioral transmission chain would be extended to include three or more nodes, and the corresponding reciprocal effects would gradually weaken (Liu et al, 2015). It is therefore worth exploring the pattern and duration of the effects of intention manipulation, which would thus have a certain value in application.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized reciprocity 1 refers to a situation whereby a person who had been treated positively or negatively by others in the past delivers a treatment following the same pattern to someone else, commonly referred to as "paying it forward" (Gray et al, 2014). As a principal component of moral codes, generalized reciprocity might induce a series of chain reactions from the initial biased behavior (e.g., Nowak and Sigmund, 2005;Liu et al, 2015). Evolutionary studies have confirmed that combined with certain behavioral strategies, generalized reciprocity could bring the benefits of generating cooperation behaviors and promoting interpersonal communication (Nowak and Roch, 2007;Rankin and Taborsky, 2009).…”
Section: Introductionmentioning
confidence: 99%